2017
DOI: 10.18632/oncotarget.18066
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced antiproliferative activity of antibody-functionalized polymeric nanoparticles for targeted delivery of anti-miR-21 to HER2 positive gastric cancer

Abstract: MiR-21 is an oncogenic miR frequently elevated in gastric cancer. Overexpression of miR-21 decreases the sensitivity of gastric cancer cells to trastuzumab, which is a humanized monoclonal antibody targeting human epidermal growth factor receptor 2. However, optimization of miRNA or its anti-miRNA oligonucleotides (AMOs) for delivery is a challenge. Receptor-mediated endocytosis plays a crucial role in the delivery of biotherapeutics including AMOs. This study is a continuation of our earlier findings involvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 37 publications
1
10
2
Order By: Relevance
“…11 In contrast, clear cell carcinoma showed poorer outcomes compared to the serous carcinoma in ESEOC patients in other studies. 17,20 The difference between the findings of this study and those of other studies could be justified by the fact that antineoplastic drug regimens affect the outcomes of different histologic types especially those of clear cell histology. 12 In contrast to previous studies, in this study, a few numbers of patients with clear cell carcinoma were included and were considered as having other types of tumors.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…11 In contrast, clear cell carcinoma showed poorer outcomes compared to the serous carcinoma in ESEOC patients in other studies. 17,20 The difference between the findings of this study and those of other studies could be justified by the fact that antineoplastic drug regimens affect the outcomes of different histologic types especially those of clear cell histology. 12 In contrast to previous studies, in this study, a few numbers of patients with clear cell carcinoma were included and were considered as having other types of tumors.…”
Section: Discussioncontrasting
confidence: 80%
“…29 The relationship between histological types and survival of EOC patients varied across studies. 2,11,17,20 The results of this research also indicated that patients with endometrioid type EOC had a worse OS than serous histological type. Also, the prognosis of the mucinous type was similar to that of the serous type.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…87 Gastric cancer tends to overexpress MiR-21; to combat this condition, Wu et al developed a novel nano-delivery system called anti-miRNA oligonucleotide-21-human epidermal growth factor receptorpoly(ethylene glycol)-poly(ε-caprolactone) nanoparticles, and then used it to encapsulate trastuzumab to target gastric cancer cells in vitro and in vivo. 88 As a result, gastric cancer cells were more sensitive to drugs, and this demonstrated the enormous potential of antibody-dependent targeted transport. In addition, Nam et al constructed a novel nanocarrier based on the mussel-inspired mineralization using calcium phosphate-assembled polymer nanocarrier to load DOX.…”
Section: Polymeric Micellesmentioning
confidence: 99%
“…89 Hu's team and Wu's team each introduced PCL-PEG nanoparticles coated with trastuzumab (HER-PEG-PCL NPs) to control the delivery of the inhibitor of miRNA. 12,90 These studies, respectively, verified the inhibitory function of miR-34a, miR-21, miR-542-3p, and miR-200c on GC in vitro or in vivo. Importantly, these strategies involve the use of synthetic nanoparticles and compounds to attempt to solve the problem of improving microRNAs-targeted transport to tumors so as to promote the clinical application of microRNA-based targeted therapies.…”
Section: Synthetic Nanoparticles and Compoundsmentioning
confidence: 75%